STRATEGI PEMBELAJARAN EKSPOSITORI UNTUK ANAK BERKEBUTUHAN KHUSUS JENIS TUNARUNGU PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Agus Supriyadi; Fera Patmawati; Iro Waziroh (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
Religious Education in Islam Learning is essential in life, thus an educator must be able to explain and present content effectively. Choose tactics and procedures based on the qualities and requirements of pupils, particularly those with exceptional needs such as deafness. The Islamic Religious Education learning strategy for deaf children with special needs at SLB Tunas Bangsa Asembagus Situbondo employs an expository learning strategy, which involves the delivery of verbal material from a teacher to a group of students and mastery of the material through learning activities. Preparation, presentation (delivery) of content, correlation, conclusion, and application precede learning. The factors that aid in learning Islamic religious education are as follows: (1) internal factors consisting of students' interest in learning and motivation. (2) external factors, namely the establishment of a harmonious relationship between teachers and students as well as between teachers and guardians of students.